2003
DOI: 10.1292/jvms.65.615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sustained Release Isosorbide Dinitrate (EV151) in Dogs with Experimentally-Induced Mitral Insufficiency

Abstract: ABSTRACT. To investigate the hemodynamic effects on seven anesthetized dogs with experimentally-induced mitral insufficiency, isosorbide dinitrate (ISDN) in sustained release form (EV151) was administered at different dosages (0, 2, 8 and 16 mg/kg). The drug administration resulted in altered pulmonary arterial wedge pressure (preload), and cardiac output and total systemic resistance (afterload). Arterial pressure increased in the control group and in animals receiving 2 mg/kg, but decreased in animals 1-2 hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
2

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
0
4
2
Order By: Relevance
“…Previous studies reported that ISDN has beneficial acute hemodynamic effects in humans and dogs with MR because of their preload and afterload reducing properties . Nagasawa et al reported that there was a slight decrease in preload and afterload at 2 mg/kg sr‐ISDN . However, in this study, there was no significant change in parameters in the 2 mg/kg group.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…Previous studies reported that ISDN has beneficial acute hemodynamic effects in humans and dogs with MR because of their preload and afterload reducing properties . Nagasawa et al reported that there was a slight decrease in preload and afterload at 2 mg/kg sr‐ISDN . However, in this study, there was no significant change in parameters in the 2 mg/kg group.…”
Section: Discussioncontrasting
confidence: 68%
“…15 Nagasawa et al reported that there was a slight decrease in preload and afterload at 2 mg/kg sr-ISDN. 12 However, in this study, there was no significant change in parameters in the 2 mg/kg group. Compared with the previous study, this study was performed in conscious dogs.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations